THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE - Darwinto, Darwinto; Amelia, Idahlia; Masripah, Ipah (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
The purpose of this study was to determine the effect of Transformational Leadership Style Variable (X) on Employee Performance (Y) with Motivation (Z) as Intervening Variable at PT JNE Gudang OTB Legok, Tangerang Regency. The method used is a quantitative method of measuring the method used is the Likert scale by taking 45 respondents from the entire population as the research sample. For data analysis, researchers used statistical analysis with the SmartPLS 3.2.9 program.  From the research results, it is known that the Transformational Leadership Style has a positive and significant effect on employee performance with the path coefficient value of 0.324 or 32.4% and has a p-value <0.05, which is 0.031. Transformational Leadership Style has a positive and significant effect on motivation with the result that the path coefficient value is 0.912 or 91.2% and has a p-value <0.05, which is 0.000. Motivation has a positive and significant effect on employee performance with the result that the path coefficient value is 0.632 or 63,2% t- and has a p-value <0.05, which is 0.000. Motivation variable shows that motivation is a partial mediation of the influence of Transformational Leadership Style on Performance, with a significance of 0.000 <0.05.